Barriers And Facilitators to Accessing Medical Services in Rural And Remote Australia: A systematic review - Harrison Thorn; Richard Olley (ACHSM, 2023)
Objective: This qualitative review aims to identify and list the barriers and facilitators to accessing medical services for rural and remote Australians, within the current literature to inform policy development and highlight the need for further research. Methods: The review was guided by the PRISMA method. Boolean search strings identified relevant articles using the Griffith University Library electronic catalogue. The study included only English language research articles published between August 31st, 2018 and August 31st, 2021, focusing on facilitators and barriers within the Australian context considering both access and rurality/remoteness. Results: Thematic analysis of six articles identified ten barriers: communication, confidentiality, fear and shame, funding, geography, health behaviours, reliance on others, service provision, staffing, transport; and eight facilitators: collaboration/partnerships, communication, cultural safety funding, service provision, staffing, and telehealth, to accessing medical services in rural and remote Australia. Conclusion: Ten barriers and eight facilitators to accessing medical services in rural and remote Australia were identified and listed from six articles identified through a qualitative review. This review identified a research gap regarding understanding the underlying challenges behind these barriers and facilitators and the implications for policy implementation to improve access to medical services.